The Role of the Visual Arts in Enhancing the Learning Process - Tyler, Christopher W.; Likova, Lora T. (Frontiers in Human Neuroscience, 2012)
Inspiration is an important aspect of the artistic experience, both for the artist and for the viewer of the work. Inspiration involves not only higher cortical circuitry but its integration with the deep brain structures such as limbic system and medial frontal structures, which are understood to mediate the experience of emotions, motivational rewards and the appreciation of the aesthetic values of the impinging stimuli. In this sense, inspiration can turn almost any occupation in life into an avocation, a source of satisfaction in achieving life goals. Conversely, when inspiration is lacking the motivation to learn, adapt and prosper is impeded. Thus, inspiration may be viewed as a vital aspect of human experience in linking art and science. There is a certain stigma associated with careers in science, as a result of the inevitable concentration on narrow specializations that are inaccessible to general understanding. If the sciences can be associated with relevant areas of artistic endeavor, they may be viewed as more accessible and more favorable as a topic of study. The enhancement of learning remains a challenge particularly in the school setting. While direct explanation seems the best approach to teaching any specific subject on the curriculum, it is well-known that the ability to absorb facts and concepts is greatly enhanced by placing them in a broader context of relevance to the issues of everyday life and the larger goals of improvement of the quality of life and human advancement to a more evolved status of society as a whole. The consequent need for research in the relationship between learning and experience in the arts is urgent because arts education and scientific literacy remain at an inadequate level and educational interventions are suboptimal.